PATIENTS’ PERCEPTION REGARDING THE ATTRIBUTES OF DOCTORS SERVING IN A GOVERNMENT HOSPITALS - Mashhod, Asher Ahmed; Khaliq, Tanwir (Pakistan Armed Forces Medical Journal, 2019)
Objective: The objective of the study was to explore the perceptions of entitled clientele regarding attributes of doctors serving in government owned hospitals. Study Design: Qualitative study. Place and Duration of Study: Government owned hospital, as part of research project for MCPS in health professional education. It was conducted from 1st Jan 2018 to 31st Jan 2018. Material and Methods: The study population consisted of different categories of patients who had been visiting various government owned hospitals, as entitled patients, in the past 3 years. The participants of the study were purposefully selected, who were educated and rich in information. The data collection tool used in the study was focused semi-structured interviews. The data collection procedure was one to one interviews in Urdu, with audio recording and later translated and written in English. Key words and important points in the text were highlighted, coded, themed and categorized. The data was analyzed manually and validated by 2 observers. Results: From 8 interviews nine themes were generated. These themes were doctors‟ attitudes, patients‟ expec-tations, patients‟ satisfaction, doctor-patient relationship, availability to patients, punctuality, professionalism, personal attire and influence of administration in doctors‟ attitude. From these themes several subthemes were derived, and their frequencies were calculated. Conclusion: It was concluded from the study that the patients visiting the government owned hospitals were satisfied as far as the communication skills, professionalism, expertise, competence and doctor-patient relation-ship, were concerned. The patients, however wanted doctors to attend them whenever they come to the hospital.........